The relationship between the monocyte-to-lymphocyte ratio and osteoporosis in postmenopausal females with T2DM: A retrospective study in Chinese population - Li, Hailin; Zhang, Xinqi; Zhang, Qi; Zhang, Qiong; Zhu, Xueying; Xie, Tuxiu; Wang, Shuo (Frontiers in Endocrinology, 2023)
Introduction The risk of fragility fractures is increased in patients with type 2 diabetes mellitus (T2DM). Many reports indicate that inflammatory and immune responses are associated with osteoporosis and osteopenia. The monocyte-to-lymphocyte ratio (MLR) is a novel potential marker of inflammatory and immune responses. The present study evaluated the associations between the MLR and osteoporosis in postmenopausal females with T2DM. Methods Data were obtained from 281 T2MD postmenopausal females, and divided into three groups: Osteoporosis group, osteopenia group and normal BMD group. Result Data analyses revealed that the MLR was significantly lower in T2MD postmenopausal females with osteoporosis than in those with osteopenia and normal BMD. Logistic regression showed that the MLR was an independent protective factor for osteoporosis in postmenopausal females with T2DM (odds ratio [OR]: 0.015, 95% confidence interval [CI]: 0.000–0.772). Based on the receiver operating characteristic (ROC) curve, the MLR for diagnosing osteoporosis in postmenopausal females with T2DM was projected to be 0.1019, an area under the curve of 0.761 (95% CI: 0.685–0.838), a sensitivity of 74.8% and a specificity of 25.9%. Conclusions The MLR have a high efficacy in diagnosis for osteoporosis in postmenopausal females with T2DM. MLR have the potential to be used as diagnosis marker for osteoporosis in postmenopausal females with T2DM.